Autochthonous starter culture selection to keep traditions in the manufacture of dry sausages alive - Palavecino Prpich, Noelia Zulema (2014)
Lactic acid bacteria (LAB) and non-pathogenic staphylococci from naturally fermented sausages manufactured in northeastern Argentina were isolated and selected on the basis of physiological, technological, and safety properties. Eighty-seven isolates recovered from four small-scale facilities were studied to evaluate growth and acidification kinetics, nitrate-reductase, proteolytic, lipolytic, decarboxylase, and antagonistic activities, as well as growth ability at different temperatures, pH, and NaCl concentrations. Based on these characteristics as well as antibiotic resistance for CNC isolates, a selection and identification by sequencing the 16S rRNA gene was carried out. As a result, LAB isolates were identified as Lactobacillus sakei (seven isolates) and Lactobacillus farciminis (one isolate), while CNC revealed isolates as being Staphylococcus xylosus (two isolates), Staphylococcus vitulinus (one isolate), and Staphylococcus hominis (one isolate). Properties exhibited by selected isolates would make them eligible as starter cultures to enhance both sensorial and safety qualities of artisanal fermented sausages while keeping manufacturing traditions.